Handbook of basic statistical concepts for scientists and pharmacists - Rani, Shubha (Alpha Science International, 2012)
For Scientists and Pharmacists explains the fundamentals of frequently used statistical methods including distributions, estimation, testing of hypothesis, correlation and regression in a very simple and understandable language. An attempt is made to emphasize the importance of identifying the problem correctly and applying appropriate statistical methods. Various examples are given to demonstrate the application of different statistical techniques depending upon the situation and pertaining objectives. It will help in developing both an understanding and appreciation of the discipline. Though the book is written with the aim of explaining basic statistical concepts to scientists and students of pharmacy, it will be useful for readers from any field or background.